Politicizing hydroelectric power plants in Portugal: Spatio-temporal injustices and psychosocial impacts of renewable energy colonialism in the Global North - Batel, S.; Küpers, S. (Globalizations, 2023)
The extent to which infrastructures being deployed for a postcarbon transition can be considered sustainable has been increasingly scrutinized within the critical turn in energy justice research. However, the focus therein tends to be on how new megaprojects still reveal Global North–Global South colonial relations and energy-related injustices. In this paper, we aim to contribute to widening critical energy justice research by illustrating how it needs to also consider the spatio-temporalities of renewable energy colonialism in the Global North. To that end, we undertake a psychosocial historiography of selected large-scale hydroelectric power plants in Portugal, from the twentieth century to the present day. This historiography is undertaken via archival data and interviews. Our analysis illustrates how hydrocolonialism has been enacted–discursively, infrastructurally, and psychosocially–in rural areas in Portugal, across different socio-political regimes; and also how it can be contested, by identifying some examples of resistance.